THE INFLUENCE OF LEADERSHIP STYLE, WORK-LIFE BALANCE AND ORGANIZATIONAL CLIMATE ON EMPLOYEE PERFORMANCE AT PT. MITRA SARANA PURNAMA - Hopipah, Zahroh; Affini, Dinar Nur (International Humanities and Applied Science Journal, 2025)
Human resources are one of the important parts of an organization. Leadership style, work-life balance, and organizational climate are needed to support employees to increase productivity and complete work in accordance with company procedures. With the implementation of an effective leadership style, a maintained work-life balance, and a conducive organizational climate, the quality of human resources will further improve and have a positive impact on employee performance. Basically, quality human resources will help PT. Mitra Sarana Purnama in achieving its strategic goals. This study aims to analyze the influence of leadership style, work-life balance, and organizational climate on employee performance at PT. Mitra Sarana Purnama. This study uses a quantitative descriptive approach with a population and sample of 95 permanent employees, because using a saturated sample technique. Data was collected through a questionnaire survey with a Likert scale of 1-5. Data analysis was carried out using the Structural Equation Model (SEM) approach with the SmartPLS analysis tool version 4.0. The results of the study show that leadership style has a positive and significant effect on employee performance. Work-life balance also has a positive and significant influence on employee performance. Similarly, the organizational climate exerts a positive and significant influence on employee performance.